The doctoral training in Physical Culture in the East University (Review) (Revista científica Olimpia, 2020)
The process of doctoral training in Physical Culture understands, specifically a readiness that matches diverse modalities but all the implied with it had named Sciences of the Culture the Physics. In the esteem state this program, named a Doctorate in Sciences of the Physical Culture, is developed by the University of Holguín. The program has as a sweeping bomb site to shape doctors in Sciences of de Culture Physical with a stalwart preparation teoric methodological, ethical and scientific had oriented solutions on problems scientific in the search of the one main in the different spheres of action and in professional's training of the Physical Culture Scientists and widening the sweeping and specialize culture of the professionals of these areas of the awareness were, in function of lending new awareness’s. The Center of Surveys of the Physical Culture and Sport, east pertenecient to the Faculty of a Physical Culture of the university, attends in Santiago of Cuba for the teachers implied in this program. The present article must promote the strategy of doctoral training of the faculty for the 2019.2025 time. He analyzes the piece of work of studies Center of the Physical Culture and Sport for the parrot of this purpose and the consequences that are achieved until present. Key words: doctoral training, Physical Culture, strategy of doctoral training
Keywords: doctoral training, physical culture, strategy of doctoral training